1999
DOI: 10.1007/s00585-999-1611-2
|View full text |Cite
|
Sign up to set email alerts
|

Testing electric field models using ring current ion energy spectra from the Equator-S ion composition (ESIC) instrument

Abstract: Abstract. During the main and early recovery phase of a geomagnetic storm on February 18, 1998, the Equator-S ion composition instrument (ESIC) observed spectral features which typically represent the di erences in loss along the drift path in the energy range (5±15 keV/e) where the drift changes from being E´B dominated to being gradient and curvature drift dominated. We compare the expected energy spectra modeled using a Volland-Stern electric ®eld and a Weimer electric ®eld, assuming charge exchange along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 13 publications
4
33
0
Order By: Relevance
“…The actual calculation is performed in two steps: (a) we first trace the observed proton distribution backward using the phase-space mapping method (e.g., Kistler et al, 1999;Ebihara et al, 2008); (b) we then perform a forward drift simulation assuming a boundary condition that is estimated from the back-tracing result. The backward tracing is necessary to estimate a proper boundary condition.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The actual calculation is performed in two steps: (a) we first trace the observed proton distribution backward using the phase-space mapping method (e.g., Kistler et al, 1999;Ebihara et al, 2008); (b) we then perform a forward drift simulation assuming a boundary condition that is estimated from the back-tracing result. The backward tracing is necessary to estimate a proper boundary condition.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Substorm dipolarization may also play an important additional role. Inner magnetospheric measurements from the CODIF instrument on Cluster (Reme et al, 1997) and on ESIC on Equator-S (e.g., Kistler et al, 1999) have revealed a wealth of dynamical behavior including anisotropic (pancake) H + distributions at low-L, as well as the importance and existence of upflowing fieldaligned O + at lower energies. However, the detailed behavior is not fully understood.…”
Section: Dynamical Behavior Of the Ring Current In The Inner Magnetosmentioning
confidence: 98%
“…Most of the full‐resolution data were specially calibrated for each interval. In addition, plasma ion data taken by the ion composition instrument, ESIC [ Kistler et al , 1999], operational after 20 January 1998, were used where available to complement the results of the magnetic field analysis. Upstream solar wind conditions were derived from Wind data.…”
Section: Data Setmentioning
confidence: 99%